miR-7b-3p Exerts a Dual Role After Spinal Cord Injury, by Supporting Plasticity and Neuroprotection at Cortical Level - Ghibaudi, Matilde; Boido, Marina; Green, Darrell; Signorino, Elena; Berto, Gaia Elena; Pourshayesteh, Soraya; Singh, Archana; Di Cunto, Ferdinando; Dalmay, Tamas; Vercelli, Alessandro (Frontiers in Molecular Biosciences, 2021)
Spinal cord injury (SCI) affects 6 million people worldwide with no available treatment. Despite research advances, the inherent poor regeneration potential of the central nervous system remains a major hurdle. Small RNAs 19-33 nucleotides in length are a set of non-coding RNA molecules that regulate gene expression and have emerged as key players in regulating cellular events occurring after SCI. Here we profiled a class of small RNA known as microRNAs (miRNAs) following SCI in the cortex where the cell bodies of corticospinal motor neurons are located. We identified miR-7b-3p as a candidate target given its significant upregulation after SCI in vivo and we screened by miRWalk PTM the genes predicted to be targets of miR-7b-3p (among which we identified Wipf2, a gene regulating neurite extension). Moreover, sixteen genes, involved in neural regeneration and potential miR-7b-3p targets, were found to be downregulated in the cortex following SCI. We also analysed miR-7b-3p function during cortical neuron development in vitro: we observed that the overexpression of miR-7b-3p was important 1) to maintain neurons in a more immature and, likely, plastic neuronal developmental phase and 2) to contrast the apoptotic pathway; however, in normal conditions it did not affect the Wipf2 expression. On the contrary, the overexpression of miR-7b-3p upon in vitro oxidative stress condition (mimicking the SCI environment) significantly reduced the expression level of Wipf2, as observed in vivo, confirming it as a direct miR-7b-3p target. Overall, these data suggest a dual role of miR-7b-3p: i) the induction of a more plastic neuronal condition/phase, possibly at the expense of the axon growth, ii) the neuroprotective role exerted through the inhibition of the apoptotic cascade. Increasing the miR-7b-3p levels in case of SCI could reactivate in adult neurons silenced developmental programs, supporting at the same time the survival of the axotomized neurons.